Zn- or Cu-containing CaP-Based Coatings Formed by Micro-Arc Oxidation on Titanium and Ti-40Nb Alloy: Part II-Wettability and Biological Performance; Materials; Vol. 13, iss. 19 - Komarova E. G. Ekaterina Gennadjevna; Sharkeev Yu. P. Yury Petrovich; Sedelnikova M. B. Mariya Borisovna; Primak O. Oleg; Epple M. Matthias; Litvinova L. S. Larisa Sergeevna; Shupletsova V. V. Valeria Vladimirovna; Malashchenko V. V. Vladimir Vladimirovich; Yurova K. A. Kristina Alekseevna; Dzyuman A. N. Anna Nikolaevna; Kulagina I. V. Irina Vladimirovna; Mushtovatova L. S. Lyudmila Stepanovna; et al. (2020, 2020)
Title screen